2021
DOI: 10.3389/fpubh.2021.681128
|View full text |Cite
|
Sign up to set email alerts
|

Formerly Incarcerated Community Health Workers Engaging Individuals Returning From Incarceration Into Primary Care: Results From the Transition Clinic Network

Abstract: Over half a million individuals return from United States prisons and millions more from jails every year, many of whom with complex health and social needs. Community health workers (CHWs) perform diverse roles to improve health outcomes in disadvantaged communities, but no studies have assessed their role as integrated members of a primary care team serving individuals returning from incarceration. Using data from participants who received primary care through the Transitions Clinic Network, a model of care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The last two studies are from the US. The study by Aminawung et al ( 2021 ) described how community health workers with histories of incarceration were integrated as care team members and supported patients during clinic visits aside from providing essential input on the design of programs and services and advocating for changes in clinic policies and practices. The study by Myers et al ( 2021 ) described Emotional CPR (eCPR), a program developed and delivered by individuals with a lived recovery experience from trauma and mental health challenges and that aimed to train community members in supporting others through mental health crises.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The last two studies are from the US. The study by Aminawung et al ( 2021 ) described how community health workers with histories of incarceration were integrated as care team members and supported patients during clinic visits aside from providing essential input on the design of programs and services and advocating for changes in clinic policies and practices. The study by Myers et al ( 2021 ) described Emotional CPR (eCPR), a program developed and delivered by individuals with a lived recovery experience from trauma and mental health challenges and that aimed to train community members in supporting others through mental health crises.…”
Section: Resultsmentioning
confidence: 99%
“…The other studies that described peer workers as partners in co-creation focused on implementation, identification of challenges and opportunities, and how collaborative practices involving peer workers unfolded. One study examined peer qualities and peer workers’ roles as integrated members of a primary care team serving individuals returning from incarceration (Aminawung et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Community health workers provide an array of education, advocacy, and systems navigation services that can lessen the common barriers experienced by the justice-involved population. Aminawung al. (2021) found that over a third of formerly incarcerated patients who met with a community health worker during the reentry period received assistance with social determinants of health such as housing, health insurance, transportation, and government benefits, addressing the basic needs highlighted by the medical and legal participants in the current study.…”
Section: Discussionmentioning
confidence: 99%